PENGARUH KINERJA USAHA JANGGELAN TERHADAP PERTUMBUHAN EKONOMI KELUARGA - Anggrianto, Dedek; Andriyani, Fitri; Cahyoningtyas, Retno; Hadi, Luqman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study was to determine the extent to which the performance of the janggelan business influences family economic growth. This study used a quantitative causality approach. Data were obtained directly from respondents through a questionnaire. This study used a Likert scale (1–5). The study was conducted in Penggung Village, Nawangan District, which is the main location of the janggelan business. The population in this study were all janggelan business actors in Penggung Village. The sampling technique used purposive sampling and obtained a sample of 101 respondents. The partial test showed that the t-value and p-value indicated that the performance of the janggelan business had a significant positive effect on family economic growth. In addition, based on the simultaneous test (F test), the research model was significant and suitable for use. The results of the model's goodness-of-fit test showed that 88.8% of family economic growth was influenced by the performance of the janggelan business, the remaining 11.2% was influenced by other variables not included in the model.